An assessment on seafood exporting and Its current status of Seamark (BD) Ltd. - Sarwar, Nuren Mahmud Ibne (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.